2011
DOI: 10.1016/j.talanta.2011.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt phthalocyanine as a biomimetic catalyst in the amperometric quantification of dipyrone using FIA

Abstract: A biomimetic sensor for the determination of dipyrone was prepared by modifying carbon paste with cobalt phthalocyanine (CoPc), and used as an amperometric detector in a flow injection analysis (FIA) system. The results of cyclic voltammetry experiments suggested that CoPc behaved as a biomimetic catalyst in the electrocatalytic oxidation of dipyrone, which involved the transfer of one electron. The optimized FIA procedure employed a flow rate of 1.5 mL min(-1), a 75 μL sample loop, a 0.1 mol L(-1) phosphate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…While the performance of the ePADs is below other references , two advantages need to be highlighted. First, ePADs were prepared and used without any modification with nanomaterials or charge transfer mediators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the performance of the ePADs is below other references , two advantages need to be highlighted. First, ePADs were prepared and used without any modification with nanomaterials or charge transfer mediators.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the LOD values achieved in our study are higher than most of the data found in the literature. As can be seen in Table S3, the LODs reported in the literature for paracetamol, metamizole and midazolam ranged between 10 À5 À10 À10 mol L À1 [59-64], 10 À5 À10 À8 mol L À1 [64][65][66], and 10 À5 À10 À7 mol L À1 [67,68], respectively. On the other hand, the detectability levels obtained for metamizole and midazolam using ePADs were slightly better than those found in two reports.…”
Section: Detection Of Analgesics and Sedation Drugs In Whiskeymentioning
confidence: 99%
See 1 more Smart Citation
“…Many ways of anchoring compounds electrochemically active on the surface have been investigated in order to shorten the distance between the oxidation-reduction sites involved in electronic transfer reactions (Willner et al, 2000;Murray et al, 1984). In the literature, carbon paste electrodes modified with different matrices were used in the determination of dipyrone, such as an anionic exchange resin charged ions with hexacyanoferrate (III) (Marcolino Jr., 2007) and carbon paste modified with cobalt phthalocyanine (Boni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dipyrone (acid 1-phenyl-2,3-dimethyl-5-pyrazolones-4-methilaminometanossulfonico) (Pereira et al, 2002), also known as metamizole, which is an analgesic, antithermic and nonsteroidal antipyretic, widely used with proven efficiency in pharmaceutical formulations (Santos et al, 2009;Amaral et al, 2009;Lucchetti et al, 2011). Various methods are employed for their determination, such as amperometry (Boni et al, 2011), flame emission spectrometry (Lyra et al, 2011), spectrophotometry (Suarez et al, 2011), cyclic voltammetry (Teixeira et al, 2009), liquid chromatography mass spectrometry (Ojha et al, 2009), among others, given that the electrochemical methods are simpler and have a good efficiency.…”
Section: Introductionmentioning
confidence: 99%